Clinical presentation, burden of disease and treatment in young-onset and late-onset rheumatoid arthritis: a matched-pairs analysis taking age and disease duration into account - Huscher, D.; Sengler, C.; Gromnica-Ihle, E.; Bischoff, S.; Eidner, T.; Ochs, W.; Richter, J.; Zink, A. (Clin Exp Rheumatol, 2013)
OBJECTIVES: The aim of this study is to compare clinical features and treatment of young onset rheumatoid arthritis with late-onset rheumatoid arthritis. METHODS: Nine thousand five hundred forty-one patients with rheumatoid arthritis (RA) enrolled in the national database of the German Collaborative Arthritis Centres in 2007-2009 were stratified by age at disease onset: up to 65 years (YORA), >65 years (LORA). To enable unbiased comparisons between the two groups despite their systematic differences in age and disease duration, we performed two separate matched-pairs analyses: the impact of current age was assessed by matching YORA and LORA patients for disease duration and sex (n=1,550 pairs). To identify the influence of disease duration, a second sample matched for age and sex (n=1,158 pairs) was drawn. RESULTS: At identical age, YORA patients had higher disease activity (DAS28), worse functional capacity and were less frequently in remission when compared with LORA patients. YORA patients also suffered more frequently from RA-related co-morbidities such as cardiovascular disease, chronic renal disease and osteoporosis. Matched for disease duration, there were no differences between the two groups concerning disease severity and remission rates, global health or pain intensity. Independent of age or disease duration, YORA patients reported more sleep disorders and fatigue. LORA patients received significantly fewer synthetic or biologic DMARDs than YORA patients. CONCLUSIONS: Duration of RA, rather than age, explains differences in disease burden between YORA and LORA patients. The lower prescription rates of synthetic and in particular biologic DMARDs, despite lower remission rates, indicate a potential treatment deficit in older patients.